The Prevalence and Risk Factors of Tracheostomal Stenosis Following Total Laryngectomy - Muhtarum Yusuf; Sofia Tiarini (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Tracheostomal stenosis (TS) following total laryngectomy is relatively common in patientsand a distressing complication with major effects on patient rehabilitation it affected 4-44% of patientsfollowing total laryngectomy worldwide. Various etiological factors and some risks have been indicated ascontributing to the onset of stenosis.Purpose: We aimed to investigate the prevalence and risk factors of tracheostomy stenosis following totallaryngectomyMethod: Tracheostomal stenosis was defined as respiratory insufficiency at rest or during exercise, difficultyin tracheal clearance due to non laminar flow, or both. Eighty data of patients were enrolled in this studyconsisting of 76 male (95.0%) and 4 females (5.0%). Baseline characteristics (BL) stage of cancer (SC), typeof surgery (TS), the onset of stenosis following surgery (OS) and risk factors (RF) from each patient wererecorded and analyzed using a pre-installed statistic software.Result: The overall prevalence of tracheostomal stenosis was 13.8% (11 of 80 patients). The prevalence andrisk factors of tracheostomal stenosis following total laryngectomy consisted of 7 hypertrophic scar patients(63.3%), 2 infection patients (18.12), and 1 radiotherapy and peristomal fat patient (9.01), respectively.Conclusion: Out of eighty patients, eleven patients indicates the characters of tracheostomal stenosisusing the bevel technique. The most common etiological factor is hypertrophic scar, followed by infection,radiotherapy and peristomal fat.